17β-Estradiol Protects against Apoptosis Induced by Levofloxacin in Rat Nucleus Pulposus Cells by Upregulating Integrin Alpha2beta1. (May 2014) - Ding, W.; Yang, S.; Ma, L.; Yang, D.
Introduction: Levofloxacin has been reported to have cytotoxicity to chondrocytes in vitro. 17β-estradiol has been widely studied for its protective effects against cell apoptosis. Based on apoptotic cell model induced by levofloxacin, the purpose of this study was to explore the underlying mechanism by which 17β-estradiol protects rat nucleus pulposus cells from apoptosis. Materials and Methods: Inverted phase-contrast microscopy, flow cytometry, and caspase-3 activity assay were used to determine apoptosis incidence induced by levofloxacin. Moreover, western blot and real-time quantitative polymerase chain reaction were used to explore the expression of integrins. Results: Levofloxacin-induced marked apoptosis, which was abolished by 17β-estradiol. Estrogen receptor antagonist, ICI182780, and functional blocking antibody to α2beta1 integrin, both prohibited the effect of 17β-estradiol. Simultaneously, levofloxacin decreased cellular binding ability to type II collagen, which was also reversed by 17β-estradiol. Integrin α2beta1 was responsible for estrogen-dependent anti-apoptosis, which was time- and dose-response effect. Conclusion: 17β-Estradiol was proved for the first time to protect rat nucleus pulposus cells against levofloxacin-induced apoptosis by upregulating integrin α2beta1 signal pathway. Disclosure of Interest None declared